Gestión logística y calidad de servicio del personal de un centro de salud en Iquitos 2025 - Santillan Pereyra, Weylerk (2025)
This research aimed to determine the relationship between logistics management and the quality of service provided by staff at a health center in Iquitos 2025. The study had a basic, non-experimental, cross-sectional design. The sample consisted of 80 employees. The results indicated that 47.5% of staff members considered logistics management to be good, and 47.5% considered the quality of service to be good. According to the dimensions, in the Purchasing Management dimension, 40.0% expressed that it is good, in the Supply Management dimension, 61.3% affirmed that it is good, in the Storage dimension, 45.0% affirmed that it is good, in the Distribution dimension, 53.8% affirmed that it is good, on the other hand, in the Service Quality Variable, the respondents answered in the Tangible Elements dimension, 51.2% confirmed that it is good, in the Reliability dimension, 50.0% confirmed that it is good, in the Responsiveness dimension, 57.5% expressed that it is good, in the Security dimension, 50.0% affirmed that it is good and finally in the Empathy dimension, 46.0% affirmed that it is good. Based on the results obtained, there is a direct relationship between logistics management and the quality of service provided by the staff at a health center in Iquitos 2025. Efficient logistics management is essential to improving the quality of service provided by staff at health centers in Iquitos.